Seguindo os passos dos griôs: a oralidade como instrumento metodológico para o ensino da História e cultura afro-brasileira e africana para crianças na Unidade de Educação Básica (UEB) Tancredo Neves – ISEMA - CAMPOS, Luanda Martins (2022)
The research deals with orality as a methodological tool for teaching Afro-Brazilian and African History and Culture to children at the Basic Education Unit (UEB) Tancredo Neves - ISEMA. The objective of the research was to investigate griô orality, with a view to the elaboration of a Pedagogical Kit with didactic guidelines for the use of griô orality in the light of Law no 10.639/03. The study is organized into six sections. The first section describes the Introduction, in which we present the theoretical, methodological and organizational configuration of the essay text. The second section deals with the conceptual foundations of children's education. The third section addresses Law no. 10,639/03, its historical assumptions and the Teaching of Afro-Brazilian and African History and Culture from the perspective of interculturality. The fourth section discusses the methodological steps of griôs, referring to memory and history. In the fifth section, we discuss empirical research, which was divided into three subsections: The characterization of UEB Tancredo Neves - ISEMA; the Research Methodology; Analysis and interpretation of research data; and the educational product; In the sixth section we present the final considerations. The main bibliographic sources used were: Ariès (2006), Bâ (2003), Candau (2000), Duarte (1993), Gomes (2012), Fleuri (2003; 2005), Marchi and Sarmento (2017), Munanga (2005) , Hampâté Bâ (2010), Meihi (2002), Nunes (2019), Rizzini (2011) and Vansina (2010). The research procedure method adopted was the Instrumental Case Study. The research participants were four teachers from the Early Years of Elementary Education (1st and 2nd years), the school manager and the pedagogical coordinator. Our data collection instruments were: systematic observation, methodological workshops, interviews, the semi-open questionnaire and photographs. The interpretation of data from the empirical research was in the form of charts, graphs, photographs and images. The empirical research was developed in four moments: systematic observation; interviews; methodological workshops; and composition of the educational product. The research concluded that the use of African orality as a teaching methodology allowed working on Afro-Brazilian and African history and culture in the light of Law no. 10.639/2003 in (UEB) Tancredo Neves - ISEMA.